Differentiation and traffic of IgM+ B cells between focal dark spots in skeletal muscle of Atlantic salmon, lymphoid and adipose tissues - Jiménez-Guerrero, Raúl; Karlsen, Christian René; Boudinot, Pierre; Afanasyev, Sergey; Mørkøre, Turid; Krasnov, Aleksei (Fish & Shellfish Immunology, 2023)
International audience Focal dark spots (DS) in farmed Atlantic salmon fillets contain a significant number of B cells as revealed by the high abundance of immunoglobulin (Ig) transcripts in transcriptome data. The immune response in DS remains unknown while they represent a major problem in commercial aquaculture. Here, we characterized the diversity and clonal composition of B cells in DS. Sixteen gene markers of immune cells and antigen presentation were analyzed with RT-qPCR. All genes expression showed a positive correlation with DS area and intensity. The flatter the DS, the higher the expression of cd28, csfr, ctla, igt, and sigm, the lower expression of cd83 and btla, and the larger the cumulative frequency within DS. The expression of most of the analyzed immune genes, including three Ig types and markers of B cells was lower in DS than in the lymphatic organs, head kidney and spleen, but significantly higher compared to skeletal muscle. High levels of ctla4 and cd28 in DS might indicate the recruitment of T cells. Sequencing of IgM repertoire (Ig-seq) assessed migration of B cells by co-occurrence of identical CDR3 sequences in different tissues. The combination of gene expression and Ig-seq revealed the presence of several stages of B cell differentiation in DS. B cells at the earliest stage, with high ratio of membrane to secretory IgM (migm and sigm), showed minor Ig repertoire overlap with other tissues. Further differentiation stage (increased sigm to migm ratio and high expression of pax5 and cd79) was associated with active movement of B cells from DS towards lymphatic organs and visceral fat. Traffic and expression of immune genes decreased at later stages. These B cells could be involved in a response directed against viruses, pathogenic or opportunistic bacteria in DS. Seven of eight fish were positive for salmon alphavirus, and levels were higher in DS than in unstained muscle. PCR with universal primers to the 16S rRNA gene did not detect bacteria in DS. Although the evolution of DS most ...